Integrating science for water security governance - Kristen M. Whitney; Rebecca M. Peters; Anil Mishra; Annalise G. Blum; Perry C. Oddo; Kate A. Brauman; Angelica L. Gutierrez; John D. Bolten; Matthew J. McCarthy; Andrés Sánchez (Global Environmental Change, 2026)

Remote Sensing for Irrigation Water Management—The State of the Art and Prospects for Near‐Future Operations - Wim G. M. Bastiaanssen; Chris Perry; Royce Dalby; Yasir Mohamed; Xueliang Cai; Poolad Karimi; IJsbrand de Jong; Pasquale Steduto; Marat Beksultanov; Christopher C. M. Neale; David Molden; Waqas Awan; et al. (Irrigation and Drainage, 2026)
A recent UN report describes many regions as facing ‘water bankruptcy, ’ a condition in which available water resources can no longer meet existing demands. In practice, this means irrigation will likely bear the greatest burden of future water‐use reductions, a complicated and fraught decision to make given its critical role in food security. This review paper highlights the growing range of information now available through remote sensing technologies to support planners, irrigation managers and farmers. These data include cropping patterns, crop yields, water consumption, farmgate water and tubewell water deliveries, soil moisture and root‐zone water storage, among others. The paper also reviews current applications of remote sensing, which remain too often constrained to the scientific community, and recommends the development and dissemination of standardized irrigation analytics and diagnostic tools. Government irrigation and water agencies are encouraged to integrate these emerging spatial data sources into both strategic planning and real‐time management from field to scheme scale and provide a stronger foundation of key performance indicator (KPI). Bridging this information gap will require startups and technology providers to translate advanced data products into practical, user‐friendly tools tailored to the needs of the irrigation sector.

Resistance exercise with combined Valsalva manoeuvre acutely increases carotid-femoral pulse wave velocity in healthy untrained individuals - Blake G. Perry; Melissa J. Perry; Riley Dixon; Michael Bush; Helen Ryan-Stewart (European Journal of Applied Physiology, 2026)
Purpose The Valsalva manoeuvre (VM) may contribute to the observed increase in pulse wave velocity (PWV) following resistance exercise (RE). However, VM use during RE is rarely reported or discussed in the literature. We compared the acute carotid-femoral PWV response before and following RE with paced breathing, RE with a VM (REVM) and the VM alone. Methods 15 healthy RE-untrained participants (female = 8) (mean ± SD: age, 24 ± 5 years; height, 171.7 ± 10.9 cm; body mass 69.6 ± 14.5 kg) completed in a randomised order (1) RE: 3 sets of 10 repetitions of 4 RE exercises at 60% of 1RM with paced breathing (2) REVM: repetition of the RE requirements with a VM during each of the last 6 repetitions of each set (3) VM: 12 sets of 6, 3 s VMs at a mouth pressure of 40 mm Hg. PWV was measured pre- and post-condition, with mean middle cerebral artery blood velocity, mean arterial blood pressure (MAP), heart rate, and partial pressure of end-tidal carbon dioxide measured during each visit. Results An interaction effect for PWV ( P = 0.024) was observed, with post hoc tests revealing increased PWV post REVM ( P = 0.006, pre 5.4 ± 0.3 vs. post 6.1 ± 0.9 cm/s) and VM ( P = 0.031, 5.7 ± 0.8 vs. 6.0 ± 1.0 cm/s), but not RE ( P = 0.957, 5.7 ± 0.6 vs. 5.7 ± 0.8). REVM produced the greatest MAP increase from baseline (Δ37 ± 15 mm Hg, P < 0.05 vs. both RE and VM). Conclusion These findings indicate that the VM contributes to the acute rise in post RE PWV when performed during RE and acutely increases PWV when performed repeatedly in isolation (Trial registration number ACTRN12624000876594, Date of registration 18/07/2024). Trial registration number ACTRN12624000876594.

Correction: Resistance exercise with combined Valsalva manoeuvre acutely increases carotid-femoral pulse wave velocity in healthy untrained individuals - Blake G. Perry; Melissa J. Perry; Riley Dixon; Michael Bush; Helen Ryan-Stewart (European Journal of Applied Physiology, 2026)

Finding needles in a haystack: measuring ambient concentrations of naturally occurring elongated mineral particles in an urban environment - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Wenxia (Wendy) Fan; Araliya de Zoysa; Cindy Z. Yi; Paul G. Young; Ayrton Hamilton; Nick Talbot; Martin Brook; Brett Wells; David E. Williams; et al. (Chemosphere, 2026)

Equine neorickettsiosis: A global perspective of the natural habitat of the bacteria and clinical disease - Luis G. Arroyo; Alexandre S. Borges; John D. Baird; Brian D. Perry; Yasuko Rikihisa; Stephen E. Greiman (Veterinary Microbiology, 2026)

Performance evaluation and process optimization of a hybrid treatment wetland for nutrient rich floriculture drainage water - Flor Louage; Perry Hoendervangers; Dion van Oirschot; Dores G. Cirne; Pieter Spanoghe; Stijn W.H. Van Hulle; Diederik P.L. Rousseau (Journal of Environmental Chemical Engineering, 2026)

Who needs closure? Estimating abundance with a Markovian availability model for geographically open removal sampling - Russell W. Perry; Adam C. Pope; A. Noble Hendrix; Joseph E. Kirsch; Bryan G. Matthias; Michael J. Dodrill (Ecology, 2026)
Removal sampling is an important method for estimating abundance, but nearly all removal models assume closure during sampling. Yet, closure may be difficult to assume, evaluate, or enforce in many settings. To address situations where populations are geographically open between each removal sample, we incorporated a Markovian availability process into an N‐mixture model framework. This model relates local abundance available for sampling to a superpopulation through recruitment of new individuals to the sampling area. To test the model, we (1) conducted parameter identifiability analysis, (2) fit the model to removal data generated from a random walk movement model, and (3) analyzed a case study of empirical removal data. Parameters were increasingly identifiable as capture probability exceeded 0.25 and removal samples increased from 3 to 6. Abundance estimates were unbiased when parameters were identifiable, except for scenarios that simulated a behavioral response to sampling. For our case study, the model estimated negligible recruitment for benthic‐oriented fishes, indicating closure, but we found evidence against closure for juvenile Chinook salmon, a highly mobile species. Our removal model allows researchers to formally test closure assumptions, to estimate the degree of closure, and to estimate abundance without bias when closure is violated.

Phylogenomics of endangered troglobiotic rove beetles (Coleoptera: Staphylinidae: Pselaphinae) from central Texas karst regions - Perry L. Wood; Donald S. Chandler; Nicholas S. Gladstone; Anna Mitelberg; Julia G. Smith; Kemble White; Jenny Wilson; Amy G. Vandergast (Conservation Genetics, 2026)
The karst habitats of central Texas, USA, are home to an array of endemic subterranean-obligate (troglobiotic) invertebrates. This includes several species of rove beetles (Coleoptera: Staphylinidae: Pselaphinae). Here we developed a molecular dataset using sequence capture of Ultra-Conserved Elements (UCEs) from the Coleoptera-UCE-1.1 K v1 baits kit. These data were used to assess species relationships and patterns of diversification in this group, specifically among species within the genera Batrisodes Reitter 1882 and Texamaurops Barr and Steeves 1963; with a specific focus on the relationships of the federally listed as endangered B. texanus Chandler 1992 and B.cryptotexanus Chandler and Reddell 2001. Our final datasets consisted of 69 individuals (two genera, Batrisodes [five species] and Texamaurops [one species], from 34 localities), and a molecular dataset of 658,560 aligned base pairs across 672 UCE loci. Concatenated and species-tree phylogenetic analyses resolved all troglobiotic taxa as a monophyletic group. Within the Travis and Williamson County troglobionts, we recovered four well-supported clades that generally follow hypothesized geologic barriers to dispersal formalized as karst fauna regions (KFRs). A northward pattern of diversification was observed among these groups: (A) Texamaurops reddelli Barr and Steeves 1963 (Jollyville Plateau KFR); (B) Batrisodes reyesi Chandler 1997 (West Cedar Park and Post Oak Ridge KFRs); (C) B. reyesi (McNeil-Round Rock KFR); (D) B. cryptotexanus + B. texanus (Georgetown and North Williamson KFRs). The morphologically defined Batrisodes texanus and B. cryptotexanus were not reciprocally monophyletic, nor clustered into two unique groups in clustering analyses of single nucleotide polymorphisms (SNPs). Rather, we found support for five major subclades and five to seven genetic clusters. These results suggest that diversification and subsequent isolation of clades may have occurred with the progressive availability of karst habitats over time in the North Williamson and Georgetown KFRs resulting from the interactions of faulting, geologic structure, and drainage basin evolution. Comparison with recent U.S. Fish and Wildlife Service cave habitat resiliency assessments indicated that four genetic clusters occur within at least partially resilient habitat, whereas three are confined to caves with low or impaired resiliency. Integrating genetic results presented here along with results of other molecular studies of co-occurring troglobiotic invertebrates supports considering additional geological substructure within the North Williamson KFR in conservation efforts for these rare and unique lineages and systems.

Towards a global barcode reference library for subterranean fauna - Michelle T. Guzik; Jake Thornhill; Mieke van der Heyde; Danielle N. Stringer; Nicole E. White; Mattia Saccò; Perry G. Beasley-Hall; Paul Nevill; Rachael A. King; Steven J.B. Cooper; Andrew D. Austin (Science of The Total Environment, 2026)

Monitoring of pesticides in the processing water and wastewater of vegetable processing companies: Sources and treatment challenges - Perry Hoendervangers; Liliane Goeteyn; Diederik P.L. Rousseau; Dores G. Cirne; Pieter Spanoghe (Journal of Environmental Chemical Engineering, 2025)

Reproductive risk of Neonicotinoids: A review of male rodent studies - Sumaiya S. Irfan; Veronica G. Sanchez; Michael S. Bloom; Helen B. Chin; Virginia Espina; Jenna R. Krall; Anna Z. Pollack; Lance A. Liotta; Melissa J. Perry (Environmental Research, 2025)

First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

Museum Genomics Reveals Temporal Genetic Stasis and Global Genetic Diversity in Arabidopsis thaliana - Lua Lopez; Patricia L. M. Lang; Stephanie Marciniak; Logan Kistler; Sergio M. Latorre; Asnake Haile; Eleanna Vasquez Cerda; Diana Gamba; Yuxing Xu; Patrick Woods; Mistire Yifru; Jeffrey Kerby; et al. (Molecular Ecology, 2025)
Global patterns of population genetic variation through time offer a window into evolutionary processes that maintain diversity. Over time, lineages may expand or contract their distribution, causing turnover in population genetic composition. At individual loci, migration, drift and selection (among other processes) may affect allele frequencies. Museum specimens of widely distributed species offer a unique window into the genetics of understudied populations and changes over time. Here, we sequenced genomes of 130 herbarium specimens and 91 new field collections of Arabidopsis thaliana and combined these with published genomes. We sought a broader view of genomic diversity across the species and to test if population genomic composition is changing through time. We documented extensive and previously uncharacterised diversity in a range of populations in Africa, populations that are under threat from anthropogenic climate change. Through time, we did not find dramatic changes in genomic composition of populations. Instead, we found a pattern of genetic change every 100 years of the same magnitude seen when comparing Eurasian populations that are 185 km apart, potentially due to a combination of drift and changing selection. We found only mixed signals of polygenic adaptation at phenology and physiology QTL. We did find that genes conserved across eudicots show altered levels of directional allele frequency change, potentially due to variable purifying and background selection. Our study highlights how museum specimens can reveal new dimensions of population diversity and show how wild populations are evolving in recent history.

Characterising the innate immune response in breech strike resistant and non-selected sheep to the sheep blowfly (Lucilia cuprina) - Sugandhika G. Welikadage; Habtamu B. Derseh; Trent Perry; Clare A. Anstead; Jean-Pierre Y. Scheerlinck; Vern M. Bowles (Veterinary Immunology and Immunopathology, 2025)

Estimating Spatially Explicit Survival and Mortality Risk From Telemetry Data With Thinned Point Process Models - Joseph M. Eisaguirre; Madeleine G. Lohman; Graham G. Frye; Heather E. Johnson; Thomas V. Riecke; Perry J. Williams (Ecology Letters, 2025)
Mortality risk for animals often varies spatially and can be linked to how animals use landscapes. While numerous studies collect telemetry data on animals, the focus is typically on the period when animals are alive, even though there is important information that could be gleaned about mortality risk. We introduce a thinned spatial point process (SPP) modelling framework that couples relative abundance and space use with a mortality process to formally treat the occurrence of mortality events across the landscape as a spatial process. We show how this model can be embedded in a hierarchical statistical framework and fit to telemetry data to make inferences about how spatial covariates drive both space use and mortality risk. We apply the method to two data sets to study the effects of roads and habitat on spatially explicit mortality risk: (1) VHF telemetry data collected for willow ptarmigan in Alaska, and (2) hourly GPS telemetry data collected for black bears in Colorado. These case studies demonstrate the applicability of this method for different species and data types, making it broadly useful in enabling inferences about the mechanisms influencing animal survival and spatial population processes while formally treating survival as a spatial process, especially as the development and implementation of joint analyses continue to progress.

Derivation of a nationwide wall-to-wall map of fuelwood potential - Leo G. Bont; Fabian Gemperle; Niál T. Perry; Marc Werder; Janine Schweier (Journal of Cleaner Production, 2025)

Water level drawdown and perennial vegetation impact litter decomposition in the sediment of a eutrophic wetland in the Netherlands - Kerstin Bouma; Mats I. Douma; G. F. Veen; Perry Cornelissen; Mennobart R. van Eerden; Elisabeth S. Bakker (Wetlands Ecology and Management, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Air Pollution and Temperature in Seizures and Epilepsy: A Scoping Review of Epidemiological Studies - Rachit Sharma; Leah H. Schinasi; Brian K. Lee; Jennifer Weuve; Marc G. Weisskopf; Perry E. Sheffield; Jane E. Clougherty (Current Environmental Health Reports, 2024)
Purpose of the Review Seizures and epilepsy can be debilitating neurological conditions and have few known causes. Emerging evidence has highlighted the potential contribution of environmental exposures to the etiology of these conditions, possibly manifesting via neuroinflammation and increased oxidative stress in the brain. We conducted a scoping review of epidemiological literature linking air pollution and temperature exposures with incidence and acute aggravation of seizures and epilepsy. We systematically searched PubMed, Embase, Web of Science, and APA PsycINFO databases for peer-reviewed journal articles published in English from inception to February 7, 2024. Recent Findings We identified a total of 34 studies: 16 examined air pollution exposure, 12 ambient temperature, and six examined both air pollution and ambient temperature. Most studies were conducted in Asia (China, Taiwan, South Korea, and Japan). Nearly all studies retrospectively derived acute (daily average), ambient, and postnatal exposure estimates from ground monitoring systems and ascertained epilepsy cases or seizure events through record linkage with medical records, health registry systems, or insurance claims data. Commonly assessed exposures were particulate matter (PM 2.5 , PM 10 ), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), carbon monoxide (CO), ozone (O 3 ), and daily mean ambient temperature. Overall, the main findings across studies lacked consistency, with mixed results reported for the associations of air pollutants and temperature metrics with both seizure incidence and acute aggravations of epilepsy.

Analysis of nonsynonymous SNPs in candidate genes that influence bovine temperament and evaluation of their effect in Brahman cattle - Gilberto Ruiz-De-La-Cruz; Ana María Sifuentes-Rincón; Francisco Alejandro Paredes-Sánchez; Gaspar Manuel Parra-Bracamonte; Eduardo Casas; David G. Riley; George A. Perry; Thomas H. Welsh; Ronald D. Randel (Molecular Biology Reports, 2024)
Background Temperament is an important production trait in cattle and multiple strategies had been developed to generate molecular markers to assist animal selection. As nonsynonymous single nucleotide polymorphisms are markers with the potential to affect gene functions, they could be useful to predict phenotypic effects. Genetic selection of less stress-responsive, temperamental animals is desirable from an economic and welfare point of view. Methods and results Two nonsynonymous single nucleotide polymorphisms identified in HTR1B and SLC18A2 candidate genes for temperament were analyzed in silico to determine their effects on protein structure. Those nsSNPs allowing changes in proteins were selected for a temperament association analysis in a Brahman population. Transversion effects on protein structure were evaluated in silico for each amino acid change model, revealing structural changes in the proteins of the HTR1B and SLC18A2 genes. The selected nsSNPs were genotyped in a Brahman population ( n = 138), and their genotypic effects on three temperament traits were analyzed: exit velocity, pen score, and temperament score. Only the SNP rs209984404-HTR1B (C/A) showed a significant association ( P = 0.0144) with pen score. The heterozygous genotype showed a pen score value 1.17 points lower than that of the homozygous CC genotype. Conclusion The results showed that in silico analysis could direct the selection of nsSNPs with the potential to change the protein. Non-synonymous single nucleotide polymorphisms causing structural changes and reduced protein stability were identified. Only rs209984404-HTR1B shows that the allele affecting protein stability was associated with the genotype linked to docility in cattle.

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Fluctuations in equine cutaneous pH and transepidermal water loss with time of day and ambient conditions - D.R. Discepolo; E. Gaare; G. Handlos; E.B. Perry (Journal of Equine Veterinary Science, 2024)

Effects of serta and sertb knockout on aggression in zebrafish (Danio rerio) - Michael Tea; Yihang Kevin Pan; Joshua G. R. Lister; Steve F. Perry; Kathleen M. Gilmour (Journal of Comparative Physiology A, 2024)

Within-field extrapolation away from a soil moisture probe using freely available satellite imagery and weather data - R. G. V. Bramley; E. M. Perry; J. Richetti; A. F. Colaço; D. J. Mowat; C. E. M. Ratcliff; R. A. Lawes (Precision Agriculture, 2024)
Recognition of the importance of soil moisture information to the optimisation of water-limited dryland cereal production has led to Australian growers being encouraged to make use of soil moisture sensors. However, irrespective of the merits of different sensing technologies, only a small soil volume is sensed, raising questions as to the utility of such sensors in broadacre cropping, especially given spatial variability in soil water holding capacity. Here, using data collected from contrasting sites in South Australia and Western Australia over two seasons, during which either wheat or barley were grown, we describe a method for extrapolating soil moisture information away from the location of a probe using freely-available NDVI time series and weather data as covariates. Relationships between soil moisture probe data, cumulative NDVI (ΣNDVI), cumulative net precipitation (ΣNP) and seasonal growing degree days (GDD) were significant ( P < 0.0001). In turn, these could be used to predict soil moisture status for any location within a field on any date following crop emergence. However, differences in ΣNDVI between different within-field zones did not fully explain differences in the soil moisture from multiple sensors located in these zones, resulting in different calibrations being required for each sensor or zone and a relatively low accuracy of prediction of measured soil moisture (R 2 adj ~ 0.4–0.7) which may not be sufficient to support targeted agronomic decision-making. The results also suggest that at any location within a field, the range of variation in soil moisture status down the soil profile on any given date will present as greater than the spatial variation in soil moisture across the field on that date. Accordingly, we conclude that, in dryland cereal cropping, the major value in soil moisture sensors arises from an enhanced ability to compare seasons and to relate similarities and differences between seasons as a guide to decision-making.

Calculating Nitrogen Uptake Rates in Forests: Which Components Can Be Omitted, Simplified, or Taken from Trait Databases and Which Must Be Measured In Situ? - Ray Dybzinski; Ella Segal; M. Luke McCormack; Christine R. Rollinson; Rosemary Mascarenhas; Perry Giambuzzi; Jamilys Rivera; Lucien Fitzpatrick; Caylin Wiggins; Meghan G. Midgley (Ecosystems, 2024)

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Is our understanding of aquatic ecosystems sufficient to quantify ecologically driven climate feedbacks? - Corday R. Selden; Richard LaBrie; Laura C. Ganley; Daniel R. Crocker; Ohad Peleg; Danielle C. Perry; Hannah G. Reich; Matthew Sasaki; Patricia S. Thibodeau; Jana Isanta‐Navarro (Global Change Biology, 2024)
The Earth functions as an integrated system—its current habitability to complex life is an emergent property dependent on interactions among biological, chemical, and physical components. As global warming affects ecosystem structure and function, so too will the biosphere affect climate by altering atmospheric gas composition and planetary albedo. Constraining these ecosystem‐climate feedbacks is essential to accurately predict future change and develop mitigation strategies; however, the interplay among ecosystem processes complicates the assessment of their impact. Here, we explore the state‐of‐knowledge on how ecological and biological processes (e.g., competition, trophic interactions, metabolism, and adaptation) affect the directionality and magnitude of feedbacks between ecosystems and climate, using illustrative examples from the aquatic sphere. We argue that, despite ample evidence for the likely significance of many, our present understanding of the combinatorial effects of ecosystem dynamics precludes the robust quantification of most ecologically driven climate feedbacks. Constraining these effects must be prioritized within the ecological sciences for only by studying the biosphere as both subject and arbiter of global climate can we develop a sufficiently holistic view of the Earth system to accurately predict Earth's future and unravel its past.

Highly dynamic evolution of the chemosensory system driven by gene gain and loss across subterranean beetles - Pau Balart-García; Tessa M. Bradford; Perry G. Beasley-Hall; Slavko Polak; Steven J.B. Cooper; Rosa Fernández (Molecular Phylogenetics and Evolution, 2024)

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Nanoscale calcium uranyl carbonate clusters in water - Samuel N. Perry; Virginia G. Rodriguez; Peter C. Burns (Chemical Geology, 2023)

Stakeholders’ perceptions of wetland conservation and restoration in Wakiso District, Uganda - Anthony Kadoma; Mia Perry; Fabrice G. Renaud (Environment, Development and Sustainability, 2023)
Natural wetlands are critically important to the lives and livelihoods of many people. Human activities result in the degradation of wetlands globally, and more so in developing countries prioritizing fast economic growth and development. With an increasing population in their immediate surroundings, wetlands in Wakiso District, Uganda, have become over-exploited to meet human needs. Policies, plans and projects have been put in place aiming at wetland conservation and restoration, but with limited stakeholder participation, have achieved limited success. Our research objective was to identify stakeholders, their perceptions, and understand the role these perceptions play in wetland conservation and restoration activities. To achieve these objectives, we used the ecosystem services concept within a qualitative, multi-site case study research approach. Findings show that stakeholders hold divergent perceptions on wetland ecosystem services, perceiving them as source of materials, fertile places for farming, cheap to buy and own, as well as being “God-given”. Furthermore, wetlands as habitats are perceived as not prioritized by central government. Implications for conservation and restoration vary with stakeholders advocating for (1) over-use, wise-use or not-use of wetlands and their resources, (2) educating and sensitization as well as (3) the implementation of the available laws and policies. This paper explores the findings and important implications for the conservation and restoration of wetlands in Wakiso District, Uganda.

Excitable systems: A new perspective on the cellular impact of elongate mineral particles - Shuyao Gu; Abby Bull; Jeneh K. Perry; Amilee Huang; Matt J. Hourwitz; Mona Abostate; John T. Fourkas; Andrey A. Korchevskiy; Ann G. Wylie; Wolfgang Losert (Environmental Research, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Effect of post-harvest processing methods on the microbial safety of edible seaweed - Jessica G. Vorse; Colleen T. Moody; Lyle C. Massoia; Jennifer J. Perry; Kristin M. Burkholder; Carrie J. Byron (Journal of Applied Phycology, 2023)
The American seaweed industry is growing, primarily into the edible sector, and more seaweed products are available for human consumption. It is necessary to evaluate the safety of industry’s current post-harvest storage and processing methods to ensure the risk of foodborne pathogens on edible seaweed remains low. We evaluated the pathogen load of edible kelp post-harvest under three different storage temperatures (4˚C, 10˚C, 20˚C) and two different drying methods (air- and freeze-drying). The focal pathogens for this research included: Listeria monocytogenes, Salmonella enterica, Staphylococcus aureus, pathogenic Escherichia coli, Vibrio vulnificus and Vibrio parahaemolyticus . We tested all six pathogens under each treatment condition on both sugar kelp ( Saccharina latissima) and rockweed ( Ascophyllum nodosum ) as these are the most commonly farmed and wild-harvested species in Maine, respectively. We inoculated a known concentration of pathogen onto freshly harvested kelp, treated it under a storage temperature or drying method, and sampled it over time to determine the impact of treatment on pathogen load. Our results showed that storage at 20˚C can lead to replication while storage at 4˚C and 10˚C halted the replication of focal pathogens. Both air-drying and freeze-drying produced significant log scale reductions in surface pathogen load for all focal pathogens. Additionally, air-drying reduced pathogen load more than freeze-drying for a majority of pathogens and storing dried kelp for 6-weeks further reduced pathogen load across all cases. These results are promising for industry as they corroborate historical evidence that current post-harvest storage and processing conditions are producing products safe for human consumption.

Electrocardiogram to Determine Mitral and Aortic Valve Opening and Closure - M. Rifqi Aufan; Zachary T. Jost; Neal J. Miller; Oleg F. Sharifov; Himanshu Gupta; Gilbert J. Perry; J. Michael Wells; Thomas S. Denney; Steven G. Lloyd (Cardiovascular Engineering and Technology, 2023)

Treatment of acid mine drainage and chromium (VI) removal using synthesised chitosan composites blended with kenaf fibre and γ-Fe2O3 nanoparticles - C. N. Nkuna; E. R. Sadiku; G. Perry; B. Oboirien; M. K. Dludlu; C. Thompson (International Journal of Environmental Science and Technology, 2023)

Influence of corn supplementation to beef cows during mid- to late-gestation: Supplementation decreases placental microvascular surface density but does not alter uterine blood flow or neonatal performance1 - A.R. Tanner; M.L. Bauer; K.C. Swanson; V.C. Kennedy; J.D. Kirsch; J. Gaspers; N. Negrin-Pereira; A.B.P. Fontoura; G.A. Perry; G. Stokka; A. Rodas-Gonzalez; A. Ward; et al. (Livestock Science, 2023)

The American Lobster Settlement Index: History, lessons, and future of a long-term, transboundary monitoring collaborative - M. Conor McManus; Damian C. Brady; Curtis Brown; Joshua T. Carloni; Melanie Giffin; Andrew G. Goode; Kristyn Kleman; Peter Lawton; Arnault Le Bris; Scott Olszewski; Derek N. Perry; Rémy Rochette; et al. (Frontiers in Marine Science, 2023)
Understanding the processes that influence recruitment variability in marine populations has been a long-standing challenge for resource management. Quantifying abundance at early life stages for marine fish and invertebrates with complex life histories can be difficult and require unconventional sampling approaches. However, the benefit of developing appropriate tools to sample early life stages is that, together with associated demographic and environmental information, the data can provide insights into the causes and consequences of recruitment variability, allowing prediction of older life stage abundance. Before the 1980s, the earliest benthic life stages of the American lobster ( Homarus americanus ) eluded quantitative field surveys. With the development of diver-based and vessel-deployed sampling methods over the past three decades, the American Lobster Settlement Index (ALSI) program has expanded into a regional, transboundary commitment to better understand lobster settlement processes and forecast future fishery trends for what has become the most valuable single-species fishery in North America. In this context, “settlement” is a shorthand for the annual recruitment of young-of-year lobster to coastal nurseries, as postlarvae settle to the seabed at the end of larval development. Here, we review the development and products of the ALSI program, first outlining the goals, methods, and data products of the program. We then highlight how the program has advanced the scientific knowledge on pre- and post-settlement processes that influence the fate of a cohort from egg hatch to harvest, which provides insight into the spawner-recruit relationship. Lastly, we provide guidance for future research recommendations building on the ALSI science to-date, some major elements of the program that have allowed for its success, and considerations for maintaining the ALSI program. By highlighting the uniqueness and contributions of the ALSI program, we hope it serves as a model for other scientists, managers, and industry collaborators aiming to understand recruitment processes for species over a broad geographic area.

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Invasion of Siberian Elm (Ulmus pumila) Along the South Platte River: the Roles of Seed Source, Human Influence, and River Geomorphology - Lindsay V. Reynolds; Laura G. Perry; Patrick B. Shafroth; Gabrielle Katz; Andrew Norton (Wetlands, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Matrix-level co-occurrence metrics are sensitive to sampling grain: a case study in species-rich shrublands - G. L. W. Perry; Ben P. Miller; Byron B. Lamont; Neal J. Enright (Plant Ecology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Floral abundance and richness drive beneficial arthropod conservation and biological control on golf courses - Adam G. Dale; Rebecca L. Perry; Grace C. Cope; Nicole Benda (Urban Ecosystems, 2020)

Cerebrovascular haemodynamics during isometric resistance exercise with and without the Valsalva manoeuvre - Blake G. Perry; Tom De Hamel; Kate N. Thomas; Luke C. Wilson; Travis D. Gibbons; James D. Cotter (European Journal of Applied Physiology, 2020)

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Neurofibromatosis type 2 discordance in monozygous twins - S. Amico; P. Smith; S. Tobi; M. Perry; A. Wallace; D. G. Evans (Familial Cancer, 2020)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

The role of reforestation in carbon sequestration - L. E. Nave; B. F. Walters; K. L. Hofmeister; C. H. Perry; U. Mishra; G. M. Domke; C. W. Swanston (New Forests, 2019)

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Divergent effects of land-use, propagule pressure, and climate on woody riparian invasion - Laura G. Perry; Lindsay V. Reynolds; Patrick B. Shafroth (Biological Invasions, 2018)

Monitoring responses to variation in food supply for a migratory waterfowl: American Black Duck (Anas rubripes) in winter - Perry S. Barboza; Dennis G. Jorde (Journal of Comparative Physiology B, 2018)

Multiple abiotic factors correlate with parallel evolution in Australian soil burrowing cockroaches - Perry G. Beasley‐Hall; Timothy R. C. Lee; Harley A. Rose; Nathan Lo (Journal of Biogeography, 2018)
Aim The ways in which abiotic factors contribute to parallel evolution—the evolution of similar, derived phenotypes in independent, closely related lineages—remain understudied. Australian cockroaches of the subfamilies Panesthiinae (“wood feeders”) and Geoscapheinae (“soil burrowers”) are two closely related groups that provide a striking example of parallel evolution of burrowing behaviour. The ancestral wood‐feeding panesthiines migrated from Asia ~20 million years ago before soil burrowing was independently acquired multiple times in the derived geoscapheines. Here, we investigate whether specific abiotic factors were associated with the parallel evolution of soil burrowing behaviour, and whether divergence events of geoscapheines from panesthiine ancestors are consistent with niche conservatism or divergence. Location The Australian mainland, including the areas in which selected Australian Panesthiinae and Geoscapheinae cockroach species are distributed. Methods We generated environmental niche models for members of the Australian Geoscapheinae and Panesthiinae using presence‐only data and abiotic variables related to temperature, precipitation, and soil composition from BioClim and the Australian Soil Resource Information System. We used an existing phylogenetic framework to compare environmental niche models and tested for niche conservatism versus divergence. Morphological convergence was assessed by a regression analysis and principal components analysis of leg segment and body dimensions in soil burrowers and wood feeders. Results We found no relationship between niche similarity and time since divergence, and only limited evidence for phylogenetic signal with respect to the environmental variables examined. We found that soil burrowing behaviour is consistently correlated with thirteen abiotic factors associated with aridity, including a wider range of temperatures and lower precipitation levels. Evidence for convergence in leg morphology and body dimensions across soil burrowers was found. Main conclusions Our results are consistent with soil burrowing behaviour evolving in response to ancient aridification events following the arrival of the Panesthiinae in Australia. Our results suggest a scenario of niche divergence between soil burrowers and each of their wood feeding sister taxa. There is evidence for morphological convergence on a “shovel‐like” protibiotarsus in the Geoscapheinae that would aid in burrowing into soil.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Monitoring dynamic spatio‐temporal ecological processes optimally - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower (Ecology, 2018)
Population dynamics vary in space and time. Survey designs that ignore these dynamics may be inefficient and fail to capture essential spatio‐temporal variability of a process. Alternatively, dynamic survey designs explicitly incorporate knowledge of ecological processes, the associated uncertainty in those processes, and can be optimized with respect to monitoring objectives. We describe a cohesive framework for monitoring a spreading population that explicitly links animal movement models with survey design and monitoring objectives. We apply the framework to develop an optimal survey design for sea otters in Glacier Bay. Sea otters were first detected in Glacier Bay in 1988 and have since increased in both abundance and distribution; abundance estimates increased from 5 otters to >5,000 otters, and they have spread faster than 2.7 km/yr. By explicitly linking animal movement models and survey design, we are able to reduce uncertainty associated with forecasting occupancy, abundance, and distribution compared to other potential random designs. The framework we describe is general, and we outline steps to applying it to novel systems and taxa.

First global molecular phylogeny and biogeographical analysis of two arachnid orders (Schizomida and Uropygi) supports a tropical Pangean origin and mid‐Cretaceous diversification - Ronald M. Clouse; Michael G. Branstetter; Perry Buenavente; Louise M. Crowley; Jesse Czekanski‐Moir; David Emmanuel M. General; Gonzalo Giribet; Mark S. Harvey; Daniel A. Janies; Alma B. Mohagan; Dave P. Mohagan; Prashant P. Sharma; et al. (Journal of Biogeography, 2017)
Aim We sought to illuminate the history of the arachnid orders Schizomida and Uropygi, neither of which have previously been subjected to global molecular phylogenetic and biogeographical analyses. Location Specimens used in this study were collected in all major tropical and subtropical areas where they are presently found, including the Americas, Africa, Australia and the Indo‐Pacific region. Methods From field‐collected specimens, we sequenced two nuclear and two mitochondrial markers, combined these with publicly available data, and conducted multi‐gene phylogenetic analyses on 240 Schizomida, 24 Uropygi and 12 other arachnid outgroups. Schizomid specimens included one specimen from the small family Protoschizomidae; other schizomid specimens were in Hubbardiidae, subfamily Hubbardiinae, which holds 289 of the order's 305 named species. We inferred ancestral areas using the Dispersal‐Extinction‐Cladogenesis model of range evolution, and we used fossil calibrations to estimate divergence times. Results We recovered monophyletic Schizomida and Uropygi as each other's sister group, forming the clade Thelyphonida, and terminals from the New World were usually positioned as the earliest diverging lineages. The ancestral area for schizomids reconstructed unambiguously to the region comprised of Mexico, Southern California and Florida (the xeric New World subtropics). Optimal trees suggested a single colonization of the Indo‐Pacific in both orders, although this did not receive bootstrap support. Molecular dating gave an Upper Carboniferous origin for each order, and a mid‐Cretaceous expansion of Schizomida, including the origin and initial diversification of those in the Indo‐Pacific. Main conclusions Ancestral area reconstructions, molecular dating and fossil evidence all support an Upper Carboniferous, tropical Pangean origin for Thelyphonida, Schizomida and perhaps Uropygi. Much of this region became unsuitable habitat for these arachnids during the breakup of Pangea, but they persisted in the area that is now Meso‐ and South America. From there they then expanded to the Indo‐Pacific, where schizomids today display an idiosyncratic combination of microendemism and long‐range dispersal.

Archipelagic genetics in a widespread Caribbean anole - R. Graham Reynolds; Tanner R. Strickland; Jason J. Kolbe; Bryan G. Falk; Gad Perry; Liam J. Revell; Jonathan B. Losos (Journal of Biogeography, 2017)
Aim We examine the influence of fluctuating sea levels in a land‐bridge archipelago on the apportioning of intraspecific genetic diversity and divergence in the widespread Puerto Rican crested anole ( Anolis cristatellus ). We compare three alternative scenarios for genetic diversification in an archipelagic species that contrast the relative influences of periodic isolation versus island connectedness driven by fluctuating sea levels. Our approach combines information from geography and population genetics to assess the influence of island size, island isolation, island historical geography, and population genetic processes such as drift on the contemporary distribution of genetic variation within and among islands. Location The Puerto Rico Bank in the Caribbean focusing primarily on the Spanish, British and U.S. Virgin Islands. Methods We used nuclear and mitochondrial DNA sequences and microsatellite genotypes sampled from A. cristatellus populations to investigate: (1) the broad‐scale pattern of phylogeographical divergence across Puerto Rico Bank islands and (2) diversification within the Virgin Islands archipelago. For the first component, we used sequence data to reconstruct the relationships among 542 samples from across the species range. For the second component, we examined the relative influences of island size, isolation, and population genetic processes on the distribution of genetic diversity across the Virgin Islands. Results In the Virgin Islands, A. cristatellus is represented by a monophyletic clade except on the island of Vieques, where two divergent clades coexist. We found evidence for non‐equilibrium dynamics in the Virgin Islands, suggesting spatial population expansion during intraglacial periods of low sea level. Main conclusions We found limited evidence that periods of island isolation affected patterns of genetic diversity and differentiation. Instead, we found that the patterns of genetic diversity and divergence in A. cristatellus in the Virgin Islands archipelago are likely shaped by long‐term persistence in the region and periods of population spatial expansion.

Palaeoecological records of coral community development on a turbid, nearshore reef complex: baselines for assessing ecological change - J. A. Johnson; C. T. Perry; S. G. Smithers; K. M. Morgan; N. Santodomingo; K. G. Johnson (Coral Reefs, 2017)

Nearshore Turbid-Zone Corals Exhibit High Bleaching Tolerance on the Great Barrier Reef Following the 2016 Ocean Warming Event - Kyle M. Morgan; Chris T. Perry; Jamie A. Johnson; Scott G. Smithers (Frontiers in Marine Science, 2017)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Commentary: On the water footprint as an indicator of water use in food production - E. Fereres; F. J. Villalobos; F. Orgaz; M. I. Minguez; G. van Halsema; C. J. Perry (Irrigation Science, 2017)

An integrated data model to estimate spatiotemporal occupancy, abundance, and colonization dynamics - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower; Trevor J. Hefley (Ecology, 2017)
Ecological invasions and colonizations occur dynamically through space and time. Estimating the distribution and abundance of colonizing species is critical for efficient management or conservation. We describe a statistical framework for simultaneously estimating spatiotemporal occupancy and abundance dynamics of a colonizing species. Our method accounts for several issues that are common when modeling spatiotemporal ecological data including multiple levels of detection probability, multiple data sources, and computational limitations that occur when making fine‐scale inference over a large spatiotemporal domain. We apply the model to estimate the colonization dynamics of sea otters ( Enhydra lutris ) in Glacier Bay, in southeastern Alaska.

Fresh Water Lens Persistence and Root Zone Salinization Hazard Under Temperate Climate - Sija F. Stofberg; Gualbert H. P. Oude Essink; Pieter S. Pauw; Perry G. B. de Louw; Anton Leijnse; Sjoerd E. A. T. M. van der Zee (Water Resources Management, 2017)

Riparian Soil Development Linked to Forest Succession Above and Below Dams Along the Elwha River, Washington, USA - Laura G. Perry; Patrick B. Shafroth; Steven S. Perakis (Ecosystems, 2017)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

Erratum to: New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

Heart rate analysis by sparse representation for acute pain detection - Shai Tejman-Yarden; Ofer Levi; Alex Beizerov; Yisrael Parmet; Tu Nguyen; Michael Saunders; Zvia Rudich; James C. Perry; Dewleen G. Baker; Tobias Moeller-Bertram (Medical & Biological Engineering & Computing, 2016)

Cerebrovascular, cardiovascular and strength responses to acute ammonia inhalation - Blake G. Perry; Hayden J. Pritchard; Matthew J. Barnes (European Journal of Applied Physiology, 2016)

Increasing a freshwater lens below a creek ridge using a controlled artificial recharge and drainage system: a case study in the Netherlands - Pieter S. Pauw; Esther S. van Baaren; Martijn Visser; Perry G. B. de Louw; Gualbert H. P. Oude Essink (Hydrogeology Journal, 2015)

The Y ersinia pestis HmsCDE regulatory system is essential for blockage of the oriental rat flea ( X enopsylla cheopis ), a classic plague vector - Alexander G. Bobrov; Olga Kirillina; Viveka Vadyvaloo; Benjamin J. Koestler; Angela K. Hinz; Dietrich Mack; Christopher M. Waters; Robert D. Perry (Environmental Microbiology, 2015)
Summary The second messenger molecule cyclic diguanylate is essential for Y ersinia pestis biofilm formation that is important for blockage‐dependent plague transmission from fleas to mammals. Two diguanylate cyclases ( DGCs ) HmsT and Y 3730 ( HmsD ) are responsible for biofilm formation in vitro and biofilm‐dependent blockage in the oriental rat flea X enopsylla cheopis respectively. Here, we have identified a tripartite signalling system encoded by the y3729‐y3731 operon that is responsible for regulation of biofilm formation in different environments. We present genetic evidence that a putative inner membrane‐anchored protein with a large periplasmic domain Y 3729 ( HmsC ) inhibits HmsD DGC activity in vitro while an outer membrane P al‐like putative lipoprotein Y 3731 ( HmsE ) counteracts HmsC to activate HmsD in the gut of X . cheopis . We propose that HmsE is a critical element in the transduction of environmental signal(s) required for HmsD ‐dependent biofilm formation.

Community structure and palaeoecological implications of calcareous encrusters on artificial substrates across a Mexican Caribbean reef - L. J. Hepburn; P. Blanchon; G. Murphy; L. Cousins; C. T. Perry (Coral Reefs, 2015)

Regional‐scale dominance of non‐framework building corals on Caribbean reefs affects carbonate production and future reef growth - Chris T. Perry; Robert S. Steneck; Gary N. Murphy; Paul S. Kench; Evan N. Edinger; Scott G. Smithers; Peter J. Mumby (Global Change Biology, 2015)
Coral cover on Caribbean reefs has declined rapidly since the early 1980's. Diseases have been a major driver, decimating communities of framework building Acropora and Orbicella coral species, and reportedly leading to the emergence of novel coral assemblages often dominated by domed and plating species of the genera Agaricia , Porites and Siderastrea . These corals were not historically important Caribbean framework builders, and typically have much smaller stature and lower calcification rates, fuelling concerns over reef carbonate production and growth potential. Using data from 75 reefs from across the Caribbean we quantify: (i) the magnitude of non‐framework building coral dominance throughout the region and (ii) the contribution of these corals to contemporary carbonate production. Our data show that live coral cover averages 18.2% across our sites and coral carbonate production 4.1 kg Ca CO 3 m −2 yr −1 . However, non‐framework building coral species dominate and are major carbonate producers at a high proportion of sites; they are more abundant than Acropora and Orbicella at 73% of sites; contribute an average 68% of the carbonate produced; and produce more than half the carbonate at 79% of sites. Coral cover and carbonate production rate are strongly correlated but, as relative abundance of non‐framework building corals increases, average carbonate production rates decline. Consequently, the use of coral cover as a predictor of carbonate budget status, without species level production rate data, needs to be treated with caution. Our findings provide compelling evidence for the Caribbean‐wide dominance of non‐framework building coral taxa, and that these species are now major regional carbonate producers. However, because these species typically have lower calcification rates, continued transitions to states dominated by non‐framework building coral species will further reduce carbonate production rates below ‘predecline’ levels, resulting in shifts towards negative carbonate budget states and reducing reef growth potential.

Extracellular H+ induces Ca2+ signals in respiratory chemoreceptors of zebrafish - Sara J. Abdallah; Michael G. Jonz; Steve F. Perry (Pflügers Archiv - European Journal of Physiology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Dietary Supplementation of Usnic Acid, an Antimicrobial Compound in Lichens, Does Not Affect Rumen Bacterial Diversity or Density in Reindeer - Trine Glad; Perry Barboza; Roderick I. Mackie; André-Denis G. Wright; Lorenzo Brusetti; Svein D. Mathiesen; Monica A. Sundset (Current Microbiology, 2014)

Rapid vertical accretion on a ‘young’ shore-detached turbid zone reef: Offshore Paluma Shoals, central Great Barrier Reef, Australia - C. T. Perry; S. G. Smithers; P. Gulliver (Coral Reefs, 2013)

Relationships between aerosols and precipitation in the southern Appalachian Mountains - G. M. Kelly; B. F. Taubman; L. B. Perry; J. P. Sherman; P. T. Soulé; P. J. Sheridan (International Journal of Climatology, 2013)
There are many uncertainties associated with aerosol‐precipitation interactions, particularly in mountain regions where a variety of processes at different spatial scales influence precipitation patterns. Statistical relationships between aerosols and precipitation were examined in the southern Appalachian Mountains to determine the seasonal and synoptic influences on these relationships, as well as the influence of air mass source region. Precipitation events were identified based on regional precipitation data and classified using a synoptic classification scheme developed for this study and published in a separate manuscript (Kelly et al . 2012). Hourly aerosol data were collected at the Appalachian Atmospheric Interdisciplinary Research ( AppalAIR ) facility at Appalachian State University in Boone, NC (1110 m asl, 36.215°, –81.680°). Backward air trajectories provided information on upstream atmospheric characteristics and source regions. During the warm season (June–September), greater aerosol loading dominated by larger particles was observed, whereas cool season (November–April) precipitation events exhibited overall lower aerosol loading with an apparent influence from biomass burning particles. A significant relationship between aerosol optical properties and precipitation intensity was observed, which may be indicative of aerosol‐induced precipitation enhancement in each season, particularly during warm season non‐frontal precipitation.

Principles of Biofouling Protection in Marine Sponges: A Model for the Design of Novel Biomimetic and Bio-inspired Coatings in the Marine Environment? - Werner E. G. Müller; Xiaohong Wang; Peter Proksch; Carole C. Perry; Ronald Osinga; Johan Gardères; Heinz C. Schröder (Marine Biotechnology, 2013)

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

Spatial and temporal variations in turbidity on two inshore turbid reefs on the Great Barrier Reef, Australia - N. K. Browne; S. G. Smithers; C. T. Perry (Coral Reefs, 2013)

Estimating rates of biologically driven coral reef framework production and erosion: a new census-based carbonate budget methodology and applications to the reefs of Bonaire - C. T. Perry; E. N. Edinger; P. S. Kench; G. N. Murphy; S. G. Smithers; R. S. Steneck; P. J. Mumby (Coral Reefs, 2012)

Follicular determinants of pregnancy establishment and maintenance - Ky G. Pohler; Thomas W. Geary; Jacqueline A. Atkins; George A. Perry; Emma M. Jinks; Michael F. Smith (Cell and Tissue Research, 2012)

To what extent do improved irrigation technologies extend aquifer life? - C. J. Perry; P. J. G. J. Hellegers (Hydrogeology Journal, 2012)

Seasonal leptin resistance is associated with impaired signalling via JAK2-STAT3 but not ERK, possibly mediated by reduced hypothalamic GRB2 protein - Alexander Tups; Sigrid Stöhr; Michael Helwig; Perry Barrett; Elżbieta Krol; Joachim Schachtner; Julian G. Mercer; Martin Klingenspor (Journal of Comparative Physiology B, 2012)

Dodo remains from an in situ context from Mare aux Songes, Mauritius - Hanneke J. M. Meijer; Arike Gill; Perry G. B. de Louw; Lars W. Van Den Hoek Ostende; Julian P. Hume; Kenneth F. Rijsdijk (The Science of Nature, 2012)

The effects of vibration therapy on muscle force loss following eccentrically induced muscle damage - Matthew J. Barnes; Blake G. Perry; Toby Mündel; Darryl J. Cochrane (European Journal of Applied Physiology, 2012)

Vulnerability of riparian ecosystems to elevated CO 2 and climate change in arid and semiarid western N orth A merica - Laura G. Perry; Douglas C. Andersen; Lindsay V. Reynolds; S. Mark Nelson; Patrick B. Shafroth (Global Change Biology, 2012)
Riparian ecosystems, already greatly altered by water management, land development, and biological invasion, are being further altered by increasing atmospheric CO 2 concentrations ([ CO 2 ]) and climate change, particularly in arid and semiarid (dryland) regions. In this literature review, we (1) summarize expected changes in [ CO 2 ], climate, hydrology, and water management in dryland western N orth A merica, (2) consider likely effects of those changes on riparian ecosystems, and (3) identify critical knowledge gaps. Temperatures in the region are rising and droughts are becoming more frequent and intense. Warmer temperatures in turn are altering river hydrology: advancing the timing of spring snow melt floods, altering flood magnitudes, and reducing summer and base flows. Direct effects of increased [ CO 2 ] and climate change on riparian ecosystems may be similar to effects in uplands, including increased heat and water stress, altered phenology and species geographic distributions, and disrupted trophic and symbiotic interactions. Indirect effects due to climate‐driven changes in streamflow, however, may exacerbate the direct effects of warming and increase the relative importance of moisture and fluvial disturbance as drivers of riparian ecosystem response to global change. Together, climate change and climate‐driven changes in streamflow are likely to reduce abundance of dominant, native, early‐successional tree species, favor herbaceous species and both drought‐tolerant and late‐successional woody species (including many introduced species), reduce habitat quality for many riparian animals, and slow litter decomposition and nutrient cycling. Climate‐driven changes in human water demand and associated water management may intensify these effects. On some regulated rivers, however, reservoir releases could be managed to protect riparian ecosystem. Immediate research priorities include determining riparian species' environmental requirements and monitoring riparian ecosystems to allow rapid detection and response to undesirable ecological change.

Implications of reef ecosystem change for the stability and maintenance of coral reef islands - Chris T. Perry; Paul S. Kench; Scott G. Smithers; Bernhard Riegl; Hiroya Yamano; Michael J. O'Leary (Global Change Biology, 2011)
Coral reef islands are among the most vulnerable environments on Earth to climate change because they are low lying and largely constructed from unconsolidated sediments that can be readily reworked by waves and currents. These sediments derive entirely from surrounding coral reef and reef flat environments and are thus highly sensitive to ecological transitions that may modify reef community composition and productivity. How such modifications – driven by anthropogenic disturbances and on‐going and projected climatic and environmental change – will impact reef island sediment supply and geomorphic stability remains a critical but poorly resolved question. Here, we review the unique ecological–geomorphological linkages that underpin this question and, using different scenarios of environmental change for which reef sediment production responses can be projected, explore the likely resilience of different island types. In general, sand‐dominated islands are likely to be less resilient than those dominated by rubble grade material. However, because different islands typically have different dominant sediment constituents (usually either coral, benthic foraminifera or H alimeda ) and because these respond differently to individual ecological disturbances, island resilience is likely to be highly variable. Islands composed of coral sands are likely to undergo major morphological change under most near‐future ecological change scenarios, while those dominated by H alimeda may be more resilient. Islands composed predominantly of benthic foraminifera (a common state through the P acific region) are likely to exhibit varying degrees of resilience depending upon the precise combination of ecological disturbances faced. The study demonstrates the critical need for further research bridging the ecological–geomorphological divide to understand: (1) sediment production responses to different ecological and environmental change scenarios; and (2) dependant landform vulnerability.

Spatial variation in porosity and skeletal element characteristics in apical tips of the branching coral Acropora pulchra (Brook 1891) - R. C. Roche; R. L. Abel; K. G. Johnson; C. T. Perry (Coral Reefs, 2011)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Remote Sensing and Economic Indicators for Supporting Water Resources Management Decisions - Petra J. G. J. Hellegers; Richard Soppe; Chris J. Perry; Wim G. M. Bastiaanssen (Water Resources Management, 2010)

Geomorphology and community structure of Middle Reef, central Great Barrier Reef, Australia: an inner-shelf turbid zone reef subject to episodic mortality events - N. K. Browne; S. G. Smithers; C. T. Perry (Coral Reefs, 2010)

Continuous transformation learning of translation invariant representations - G. Perry; E. T. Rolls; S. M. Stringer (Experimental Brain Research, 2010)

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Immobilizing nitrogen to control plant invasion - Laura G. Perry; Dana M. Blumenthal; Thomas A. Monaco; Mark W. Paschke; Edward F. Redente (Oecologia, 2010)

Nicotine self-administration in the rat: effects of hypocretin antagonists and changes in hypocretin mRNA - Mark G. LeSage; Jennifer L. Perry; Catherine M. Kotz; David Shelley; William A. Corrigall (Psychopharmacology, 2010)

Long-term coral community records from Lugger Shoal on the terrigenous inner-shelf of the central Great Barrier Reef, Australia - C. T. Perry; S. G. Smithers; K. G. Johnson (Coral Reefs, 2009)

Native cover crops suppress exotic annuals and favor native perennials in a greenhouse competition experiment - Laura G. Perry; Spencer A. Cronin; Mark W. Paschke (Plant Ecology, 2009)

Stabilisation of intertidal cobbles and gravels by Goniastrea aspera: an analogue for substrate colonisation during marine transgressions? - Chris T. Perry; Scott G. Smithers (Coral Reefs, 2009)

Combining remote sensing and economic analysis to support decisions that affect water productivity - P. J. G. J. Hellegers; R. Soppe; C. J. Perry; W. G. M. Bastiaanssen (Irrigation Science, 2009)

Filling the gap: improving estimates of working tree resources in agricultural landscapes - C. H. Perry; C. W. Woodall; G. C. Liknes; M. M. Schoeneberger (Agroforestry Systems, 2009)

Observations of pigment and particle distributions in the western North Atlantic from an autonomous float and ocean color satellite - E. Boss; D. Swift; L. Taylor; P. Brickley; R. Zaneveld; S. Riser; M. J. Perry; P. G. Strutton (Limnology and Oceanography, 2008)
Profiling floats with optical sensors can provide important complementary data to satellite ocean color determinations by providing information about the vertical structure of ocean waters, as well as surface waters obscured by clouds. Here we demonstrate this ability by pairing satellite ocean color data with records from a profiling float that obtained continuous, high‐quality optical data for 3 yr in the North Atlantic Ocean. Good agreement was found between satellite and float data, and the relationship between satellite chlorophyll and floatderived particulate backscattering was consistent with previously published data. Upper ocean biogeochemical dynamics were evidenced in float measurements, which displayed strong seasonal patterns associated with phytoplankton blooms, and depth and seasonal patterns associated with an increase in pigmentation per particle at low light. Surface optical variables had shorter decorrelation timescales than did physical variables (unlike at low latitudes), suggesting that biogeochemical rather than physical processes controlled much of the observed variability. After 2.25 yr in the subpolar North Atlantic between Newfoundland and Greenland, the float crossed the North Atlantic Current to warmer waters, where it sampled an unusual eddy for 3 months. This anticyclonic feature contained elevated particulate material from surface to 1000‐m depth and was the only such event in the float's record. This eddy was associated with weakly elevated surface pigment and backscattering, but depthintegrated backscattering was similar to that previously observed during spring blooms. Such seldom‐observed eddies, if frequent, are likely to make an important contribution to the delivery of particles to depth.

Insights into Yersinia pestis biofilm development: topology and co‐interaction of Hms inner membrane proteins involved in exopolysaccharide production - Alexander G. Bobrov; Olga Kirillina; Stanislav Forman; Dietrich Mack; Robert D. Perry (Environmental Microbiology, 2008)
Summary Primarily, three operons, hmsHFRS, hmsT and hmsP , are responsible for the development of a Yersinia pestis biofilm, which is essential for blockage‐dependent transmission of plague from fleas to mammals. Here, using specific antibodies, a polymeric β‐1,6‐ N ‐acetyl‐ d ‐glucosamine‐like polysaccharide was detected in the extracellular matrix of hmsHFRS ‐dependent Y. pestis biofilm. The production of this exopolysaccharide (EPS) was controlled by diguanylate cyclase HmsT and EAL domain phosphodiesterase HmsP, acting as positive and negative regulators respectively. Cellular compartmentalization of soluble segments of Hms inner membrane proteins, including the putative glycosyltransferase domain of HmsR, the diguanylate cyclase/GGDEF domain of HmsT and the phosphodiesterase/EAL domain of HmsP, was determined by a combination of topology prediction algorithms and construction of C‐terminal translational fusions with β‐galactosidase and alkaline phosphatase. Multiple interactions of Hms inner membrane proteins were detected using bacterial cAMP based two‐hybrid system. Biochemical analyses confirmed some of these protein–protein interactions. Our results indicate that synthesis and regulation of the Y. pestis biofilm EPS occurs in the cytoplasm by a proposed Hms enzymatic complex.

An extract of Salvia (sage) with anticholinesterase properties improves memory and attention in healthy older volunteers - Andrew B. Scholey; Nicola T. J. Tildesley; Clive G. Ballard; Keith A. Wesnes; Andrea Tasker; Elaine K. Perry; David O. Kennedy (Psychopharmacology, 2008)

Concentrations of the Allelochemical (±)-Catechin IN Centaurea maculosa Soils - Laura G. Perry; Giles C. Thelen; Wendy M. Ridenour; Ragan M. Callaway; Mark W. Paschke; Jorge M. Vivanco (Journal of Chemical Ecology, 2007)

First EFSA experiences with monitoring plans - Detlef Bartsch; A. Gathmann; S. Hartley; N. B. Hendriksen; R. Hails; K. Lheureux; J. Kiss; S. Mesdagh; G. Neemann; J. Perry; S. Renckens; J. Schiemann; et al. (Journal of Consumer Protection and Food Safety, 2007)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

Groundwater abstraction impacts on spring flow and base flow in the Hillsborough River Basin, Florida, USA - Kenneth A. Weber; Robert G. Perry (Hydrogeology Journal, 2006)

Debate: “Is Increasing Neuroinflammation Beneficial for Neural Repair?” - Keith A. Crutcher; Howard E. Gendelman; Jonathan Kipnis; J. Regino Perez-Polo; V. H. Perry; Phillip G. Popovich; Lynne C. Weaver (Journal of Neuroimmune Pharmacology, 2006)

Abnormal leaf formation in soybean: genetic and environmental effects - James H. Orf; Kevin Chase; James Specht; Ik-Young Choi; Perry B. Cregan; Karl G. Lark (Theoretical and Applied Genetics, 2006)

Overexpression of GRK2 in alzheimer disease and in a chronic hypoperfusion rat model is an early marker of brain mitochondrial lesions - Mark E. Obrenovich; Mark A. Smith; Sandra L. Siedlak; Shu G. Chen; Jack C. De La Torre; George Perry; Gjumrakch Aliev (Neurotoxicity Research, 2006)

Light competition for invasive species control: A model of cover crop–weed competition and implications for Phalaris arundinacea control in sedge meadow wetlands - Laura G. Perry; Susan M. Galatowitsch (Euphytica, 2006)

Zinc Toxicity Thresholds for Reclamation Forb Species - Mark W. Paschke; Laura G. Perry; Edward F. Redente (Water, Air, & Soil Pollution, 2006)

Learning invariant object recognition in the visual system with continuous transformations - S. M. Stringer; G. Perry; E. T. Rolls; J. H. Proske (Biological Cybernetics, 2006)

Predicting Cotton Lint Yield Maps from Aerial Photographs - G. Vellidis; M. A. Tucker; C. D. Perry; D. L. Thomas; N. Wells; C. K. Kvien (Precision Agriculture, 2004)

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

The influence of light availability on competition between Phalaris arundinacea and a native wetland sedge - Laura G. Perry; Susan M. Galatowitsch (Plant Ecology, 2004)

The genetic architecture of correlations among growth‐related traits and male age at maturation in rainbow trout - C. J. Martyniuk; G. M. L. Perry; H. K. Mogahadam; M. M. Ferguson; R. G. Danzmann (Journal of Fish Biology, 2003)
Heritabilities and genetic correlations among growth‐related traits of two cultured strains (Rainbow Springs and Spring Valley) of rainbow trout Oncorhynchus mykiss were estimated using restricted maximum likelihood methods with a three‐generation pedigree. Heritability was high (>0·50 ± 0·03) for body mass and condition factor but moderate (0·35 ± 0·04) for age at sexual maturity in males. Body mass and age at sexual maturation were phenotypically correlated in the families of one experimental strain, Rainbow Springs, and had a positive genetic correlation (0·26 ± 0·03) across families from both test strains (Rainbow Springs and Spring Valley). This indicates that faster growing individuals were more likely to mature at 2 years of age than slower growing individuals in the two hatchery strains investigated. Microsatellite markers of body mass quantitative tract loci (QTL) were reconfirmed as being located on linkage groups B, G, N, 5 and new markers on Oi were detected. Some QTL effects were restricted to specific sampling dates suggesting temporal expression of QTL. QTL for condition factor were limited to linkage group G in both strains. Three suggestive QTL for precocious maturation mapped to similar regions as those for body mass in the Rainbow Springs families while no associations were evident in the Spring Valley families. The results suggest that these regions may play a role in the basis for genetic and phenotypic correlations between body mass and precocious maturation in this species.

The Impact of Tick Control on the Productivity of Indigenous Cattle under Ranch Conditions in Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.N. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Tropical Animal Health and Production, 2003)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

In vitro Regulation of β-adrenoceptor Signaling in the Rainbow Trout, Oncorhynchus mykiss - J.G. Nickerson; G. Drouin; S.F. Perry; T.W. Moon (Fish Physiology and Biochemistry, 2002)

Planktonic copepods from temporary marshes in Everglades National Park (Florida, U.S.A.) - M. C. Bruno; G. Sagnotti; S. A. Perry (Hydrobiologia, 2002)

Preface - Xianglin Shi; Vince Castranova; Val Vallyathan; William G. Perry (Molecular and Cellular Biochemistry, 2001)

Paleogenetic evidence for a past invasion of Onondaga Lake, New York, by exotic Daphnia curvirostris using mtDNA from dormant eggs - Meghan A. Duffy; Linda J. Perry; Colleen M. Kearns; Lawrence J. Weider; Nelson G. Hairston, (Limnology and Oceanography, 2000)
Cladocerans possess traits such as resistant diapausing eggs and rapid parthenogenetic reproduction that make them efficient invaders of new habitats. Nearly all known invasions have been successful, perhaps because failed invasions are difficult to detect. It is possible, however, to identify past failed invasions, by studying the diapausing egg bank. Daphnia ephippia were found in the sediments of Onondaga Lake, New York that could neither be hatched nor identified using egg‐case morphology. Instead, we used sequences of the 12S ribosomal ribonucleic acid (rRNA) gene of mitochondrial deoxyribonucleic acid (mtDNA) extracted from diapausing eggs to identify the unknown Daphnia . We compared these DNA sequences with those generated from morphologically identified Daphnia species collected in Onondaga Lake, and with published sequences for other North American Daphnia species. The invader was identified as Daphnia curvirostris , a Eurasian species that has been only reported once before from North America, in extreme northwestern Canada. The discovery of it in Onondaga Lake signifies a greater than 4,500‐km range extension for this species. On the basis of the sediment ephippial data, D. curvirostris first appeared in the lake about 1952, reached maximum abundance during the period of peak pollution (1950s–1980s), and then essentially disappeared after 1983 when lake water quality improved. As with the finding of another exotic cladoceran, D. exilis , in Onondaga Lake (Hairston et al. 1999 a ), it is likely that chemical industry activities on the lakeshores were the original source of invading D. curvirostris , that pollution allowed this species to become established in the lake, and that the reduction in pollution ultimately led to its disappearance from the water column.

DNA sequence analysis identifies genetically distinguishable populations of harp seals ( Pagophilus groenlandicus ) in the Northwest and Northeast Atlantic - E. A. Perry; G. B. Stenson; S. E. Bartlett; W. S. Davidson; S. M. Carr (Marine Biology, 2000)

Population biology of a failed invasion: Paleolimnology of Daphnia exilis in upstate New York - Nelson G. Hairston; Linda J. Perry; Andrew J. Bohonak; Meghan Q. Fellows; Colleen M. Kearns; Daniel R. Engstrom (Limnology and Oceanography, 1999)
Viable diapausing eggs of Daphnia exilis , a species within the Daphnia similis species complex, occur in sediments of Onondaga Lake, New York. The discovery of this species, which otherwise occurs exclusively in temporary saline ponds in southwestern North America, represents a range extension of 1,000 km. 210 Pb‐dating of the sediments containing diapausing eggs indicates that D. exilis was present in Onondaga Lake between the mid‐1920s and the early 1980s. The species' introduction, successful colonization, and subsequent disappearance from the water column correspond temporally with distinct events in the history of industrial activity along the shores of the lake and with the paleoecological record of this activity deposited in Onondaga Lake sediments. Only the most recently deposited diapausing eggs (late 1970s to early 1980s) hatch during laboratory incubation; older eggs may not be viable because of toxic concentrations of mercury pollution in older sediments. The D. exilis eggs that have hatched have had strikingly low genetic (allozyme) variation in comparison with the variation documented for populations in the southwestern United States by Hebert and Finston (1993). Exploration of various invasion scenarios through simulated introduction of genotypes from the southwestern United States suggests that a single genotype established the D. exilis population in Onondaga Lake. These observations document the ecological and microevolutionary patterns associated with an invasion by an exotic crustacean that currently persists only in the sediment egg bank.

Biologically active compounds from Ozothamnus leptophyllus - Jacqueline E. Wood; Murray H. G. Munro; John W. Blunt; Nigel B. Perry; John R.L. Walker; Josephine M. Ward (New Zealand Journal of Botany, 1999)
A crude extract from a New Zealand native plant, Ozothamnus leptophyllus , was shown to possess antifungal activity. Flavonoids, mainly chalcones in the leaf exudate, were isolated, some of which possessed antiviral as well as antifungal activity. These flavanoids are excreted by glandular trichomes and form quasi‐crystalline deposits on the abaxial side of the leaves. 2’,4’,6'‐Trihydroxy‐chalcone was found to be active against both Polio virus (Pfizer vaccine strain) and Herpes simplex type 1 (ATCC VR 733); it was also responsible for anti‐dermatophytic activity against Trichophyton mentagrophytes . 2’,4'‐Dihydroxy‐4'‐methoxy‐dihydrochalcone was also active against both viruses.

Population dynamics of ticks on indigenous cattle in a pastoral dry to semi-arid rangeland zone of Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.M. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Experimental and Applied Acarology, 1999)

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Lipids of the marine bacterium Flexibacter polymorphus - R. B. Johns; G. J. Perry (Archives of Microbiology, 1977)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)